CONTROL LABORATORY BENCH OF MANIPULATOR MP-9C WITH THE HELP OF MATHEMATICAL MODELING PACKAGE - Orlovskyi, I. A. (Radio Electronics, Computer Science, Control, 2013)
An important component of student learning process automation systems is to provide skills installation, commissioning, maintenance and use of theoretical knowledge in the projects of modernization of equipment. To improve laboratory practice in the Zaporozhye National Technical University in the department of industrial electric and automation systems with the participation of students developed computer control (using the theory of discrete automata) of the package Simulink of Matlab laboratory bench manipulator MP-9C. Technical description is given of the laboratory bench, consisting of: the mechanical part of the robot arm, pneumatic, manipulator control system for logic elements, position sensors, remote control, connector board and the computer. Modernization of the stand allowed by the developed technique to improve student learning devices and features computer control arm, as well as the practical application of the theory of synthesis of discrete automata.